Penegakan Hukum atas Praktik Illegal Fishing di Indonesia Sebagai Perlindungan Wilayah Perairan Indonesia - Muhammad Iqbal Baiquni; Ahsana Nadiyya Nadiyya; Heni Rosida Rosida (Journal of Judicial Review, 2020)
Indonesia is an archipelago with a waters area that is larger than the land area. The vast area of these waters certainly produces abundant marine wealth for Indonesia. Marine wealth is a strategic potential for national economic development. Besides that, Indonesia is often faced with various security problems and law violations in Indonesia's territorial sea. Nowadays there are many cases of foreign vessels carrying out illegal fishing in Indonesian waters. Illegal fishing is an irresponsible fishing activity that has resulted in a drastic decrease in fish stocks. This is a big challenge for Indonesia in maintaining its territorial waters. Indonesia as a subject of international law certainly has the highest authority within its territorial boundaries. Therefore, it is necessary to review illegal fishing cases both from the perspective of international law and Indonesian national law.